Inter-regional disparity in soil fertility status of Southern Kerala-A statistical analysis - Nayana Narayanan (Department of agricultural statistics, College of Agriculture, 2020)
ABSTRACT The research work entitled ‘Inter-regional disparity in soil fertility status of southern Kerala – a statistical analysis’ was carried out at College of Agriculture Vellayani during 2018-2020. The objective was to develop soil fertility status index to assess regional disparity among the panchayats of Thiruvananthapuram, Kollam and Pathanamthitta districts of southern Kerala and to classify the panchayats based on soil fertility index. Secondary data on 12 soil fertility parameters, collected as a part of Kerala State Planning Board Project conducted in 2013 were used for the analysis. Detection and elimination of outliers using box plot was the first step in the analysis followed by estimation of mean vector of 12 soil fertility parameters from 43 panchayats of Kollam, 50 panchayats of Pathanamthitta and 44 panchayats of Thiruvananthapuram. The descriptive statistics used include range, mean and coefficient of variation (CV) of all the parameters. The entire analysis was done with the help of SPSS software. Among the 12 soil fertility parameters the range of Cu (0.34 - 49.89 mg kg-1), S (0.19 - 91.78 mg kg-1) Fe (7.07 - 391.84 mg kg-1) and K (17.49 - 851.85 kg ha-1) was observed to be very high with CV 249.62, 188.98, 154.22 and 92.32 per cent respectively in Kollam district. This is an indication of deficiency to above adequate availability of these nutrients in the panchayats. Among all the parameters highest consistency was observed in pH with mean value of 6.01 and the values varied between 4.66 and 8.13. EC values varied between 0.03 and 0.73dS m-1 showing a mean valueof 0.17 dS m-1 with a CV of 72.03 per cent. Almost a similar CV was observed for both OC (40.45 %) and P (44.94 %) with their values in the range 0.46 to 2.06 per cent and 9.67 to 111.49 kg ha-1 respectively. There observed a wide spread deficiency of Ca and Mg in almost all the panchayats. Among the micronutrients considered highest consistency was shown by B with a CV of 39.78 per cent and the lowest observed value of B was 0.13 mg kg-1 and the highest was 1.17 mg kg-1. Mean value of Mn was 17.47 mg kg-1 with a CV of 63.59 per cent. Available content of Mn varied between 2.33 and 46.32mg kg-1. PCA (Principal Component Analysis) performed on the mean vector of 12 soil fertility parameters of 43 panchayats in Kollam, extracted four PCs which accounted for 72.73 per cent variation of the data and based on the extracted PCs weighted aggregate index known as Soil Fertility Index (SFI) was developed to quantify the soil fertility status. The SFI thus estimated varied from 16.34 to 435.12 in Kollam with a mean of 111.31 and CV of 82.45 per cent. Further, factor analysis was performed to reduce the dimension and the soil nutrients P, Ca, K, OC, Fe, S and Cu had loading above 0.5 with a communality of more than 50 percent were retained and PCA was repeated and SFI was re-estimated. The estimated SFI was normalized using min-max normalization and based on this, the panchayats were grouped into four categories as low (SFI from 0-25%), medium (25-50%), high (50-75%) and very high (75-100%). In Kollam about 70 per cent of the panchayats were included in low fertility class with respect to initial SFI and 79 per cent with respect to SFI- FA. The soils in the panchayats listed in the low fertile category reported to have deficiency in Ca, Mg, S and Cu. While considering Pathanamthitta, EC has shown highest CV with its values range from 0.06 to 2.75 dS m-1. All the soil nutrients except B and Mg were adequate in the soils of most of the Panchayats in Pathanamthitta. pH was said to have high consistency with a CV of 8.92 per cent with its values in the range 4.20 to 6.56. CV of 27.70 and 28.80 per cent were observed for OC and K respectively with their values in the range of 0.64 to 3.26 per cent and 148.32 to 475.67 kg ha-1. CV of P was 61.85 per cent with mean value 66.62 kg ha-1. Lowest observed value of P was 4.63kg ha-1 and highest was 195.87 kg ha-1. Ca content had shown variation from 82.10 to 1000.00 mg kg-1. Mean value of Ca was 634.92 mg kg-1 with a CV of 48.60 per cent. Values of Mg were in the range of 26.62 to 461.50 mg kg-1showing 94.30 per cent CV. CV of S was 36.89 per cent with mean value 20.60 mg kg-1. A CV of 102.39 per cent was observed for B with values in the range 0.05 to 3.06 mg kg-1. CV of Cu and Fe was 35.86 per cent (for values between 0.87 to 5.51 mg kg-1) and 41.56 per cent (values in the range 20.27 to 101.62mg kg-1) respectively with their mean values as 2.73 mg kg-1 and 35.20 mg kg-1. Values of available Mn varied between 3.73 to 69.88 mg kg-1 with a CV of 63.17 per cent. PCA extracted four PCs which accounted for 68.70 per cent variation in the data. The mean and CV of the estimated SFI of Panchayats were respectively 131.75 and 33.49 based on initial PCA. The parameters OC, Cu, K, B and Mn were exempted based on factor analysis and the mean and CV of SFI- FA was respectively 185.90 and 38.30 per cent. Classification based on SFI- FA has shown an improvement in fertility status and the results of classification revealed that about 56 percent Panchayats were in high to very high soil fertility category in Pathanamthitta.This was because the relatively good availability of most of the soil parameters like OC, P, K, S, Cu, Fe and Mn in the panchayats of Pathanamthitta. In Thiruvananthapuram also more consistency was shown by pH with a CV of 3.67 per cent with values in the range 5.01 to 6.32. Most of the soil fertility parameters except EC (152.15%), Cu (130.98%), K (80.66%), B (54.24%) and Fe (59.15%) were found to have CV below 50 percent indicating less variability among the Panchayats in Thiruvananthapuram. The range of values of OC and P were respectively 0.48 to 1.70 percent, 13.11 to 38.94 kg ha-1. CV of Ca was 34.94 per cent with majority of the panchayats having available Ca above 300 mg kg-1. For Ca, lowest value observed was 170.80 mg kg-1 and highest value was 882.50 mg kg-1. Mg availability varied between 29.60 to 200.79 mg kg-1 and that of S was 12.00 to 61.38 mg kg-1. There noticed an adequacy in Fe and Mn availability but B was deficient. PCA extracted five PCs which accounted for 75.06 per cent variation in Thiruvananthapuram. SFI constructed had a mean of 95.93 with a CV of 27.68 per cent. The result of factor analysis concluded that all the parameters were found to be relevant in explaining the variation in soil fertility. Based on SFI, it was observed that 51.35 percent of panchayats in Thiruvananthapuram were in the medium fertility status category with almost all the parameters were found to be sufficiently available in most of the panchayats except B and Mg in Thiruvananthapuram. The results of the study based on the developed SFI confirmed inter-regional disparity between panchayats within in each district as well as between districts. The soil fertility status of panchayats in Kollam was poor as compared to Panchayats in Pathanamthitta and Thiruvananthapuram, but soil fertility status of Panchayats in Thiruvananthapuram was low as compared to Pathanamthitta and this conclusion was statistically supported by Kruskal-Wallis test.